Synthesis and Study of Reducing the Corrosive Activity of Motor Fuels Using Additives of the MEE Series (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This scientific work proposes a method for the effective synthesis of bis-carbamate MEE-2. The physicochemical parameters and vibrational spectra of the molecule were studied and the anti-corrosion properties for motor fuels were investigated. It was revealed that the authors' synthesis method is resource-saving, energy-saving and environmentally friendly. IR spectra data prove the structure and composition of the MEE-2 molecule. Studies on the corrosion activity of fuels showed that when bis-carbamate MEE-2 was added to the fuel, the copper plate was clean and corresponded to class 1, which allows it to be used as an anti-corrosion additive for motor fuels.